The Influence of K-Pop Idols on Purchase Intention of Ultra Milk Products - Alfin Mintaro Makruf; Raden Roro Ratna Roostika (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the influence of K-Pop idols as brand ambassadors for Ultra Milk on consumer purchase intention by examining the roles of advertising content value, influencer credibility, video attitude, brand attitude, and social shopping. Research Methodology: A quantitative research approach was employed through an online questionnaire distributed to 232 Ultra Milk consumers in Indonesia who were aware of the brand’s collaborations with K-Pop idols ITZY and Stray Kids. Data were analyzed using SmartPLS software with the PLS-SEM method to test the structural relationships among the studied variables. Results: The results indicate that advertising content value and influencer credibility positively affect video and brand attitudes, both of which further enhance social shopping behavior and purchase intention. Moreover, video and brand attitudes mediate the relationships between advertising content value, influencer credibility, and social shopping. Conclusion: The study concludes that using K-Pop idols as brand ambassadors effectively enhances brand perception and consumer engagement, thereby increasing purchase intention in digital marketing contexts. Limitations: The study’s findings are limited to Indonesian consumers familiar with Ultra Milk’s collaboration with K-Pop idols, which may restrict broader generalization to other populations or product categories. Contribution: This research enriches consumer behavior and digital marketing literature by providing evidence of how global influencer collaborations strengthen local brand equity and drive purchase intentions, offering strategic insights for marketers operating in emerging markets.